2020
DOI: 10.1371/journal.pone.0221607
|View full text |Cite|
|
Sign up to set email alerts
|

Pollen morphology of Polish species from the genus Rubus L. (Rosaceae) and its systematic importance

Abstract: The genus Rubus L. (Rosaceae) not been investigated satisfactorily in terms of palynology. This genus is taxonomically very difficult due to the large number of species and problems with their delimitation, as well as very different distribution areas of particular species. The aim of this study was to investigate pollen morphology and for the first time the ranges of intrageneric and interspecific variability of Rubus species, as well as verify the taxonomic usefulness of these traits in distinguishing studie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 38 publications
(76 reference statements)
5
21
0
Order By: Relevance
“…The thickness of the exine in the grains was lower in ‘Laszka’, ‘Radziejowa’, ‘Pokusa’, and ‘Polka’ were close to the values, but in the case of ‘Polana’ it was in the range of values determined in other Rubus species (0.9–2.4 μm) [ 64 , 73 , 74 , 78 , 79 , 105 ]. Sporopollenin contributes to high exine stability.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The thickness of the exine in the grains was lower in ‘Laszka’, ‘Radziejowa’, ‘Pokusa’, and ‘Polka’ were close to the values, but in the case of ‘Polana’ it was in the range of values determined in other Rubus species (0.9–2.4 μm) [ 64 , 73 , 74 , 78 , 79 , 105 ]. Sporopollenin contributes to high exine stability.…”
Section: Discussionsupporting
confidence: 69%
“…The morphology study of the pollen grains of the six R. idaeus cultivars showed a length of the polar (P) and equatorial (E) axes of P × E: 23.8–29.5 × 21.4–28.6 µm. These values were similar or higher to those described in the literature for R. idaeus and other Rubus species, e.g., R. copelandii , R. helvellicus , R. saxatilis, R. acuminatissimus , R. apricus , R. chrysogaeus , R. clementis , R. diclinis , R. ellipticus , R. ferdinandi-muelleri , R. fraxinifolius , R. gracilis , R. megacarpus , R. montis-wilhelmi , R. niveus , R. novoguineensis , R. papuanus , R. royenii , and R. trigonus [ 60 , 64 , 73 , 74 , 75 ]. The values were lower than those reported for e.g., R. acanthodes , R. alpestris , R. archboldianus, R. buergeri , R. calycinus , R. chamaemorus L., R. lainzii , R. lorentzianus , R. macgregrii , R. moluccanus , R. pectinellus , R. praecox ., and R. seebergensis [ 60 , 64 , 73 , 75 , 78 , 98 , 106 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, among the random effects describing the phylogenetic relatedness of the species studied, the most important ranks were those of subgenus and series, while the least were those of section (Table 4). In contrast, the latest palynological study on Rubus (Lechowicz et al 2020) revealed a low agreement between pollen morphological differentiation and taxonomic division. Pollen traits were most useful at the species level.…”
Section: Discussionmentioning
confidence: 88%
“…small-sized), with tricolporate or tricolpate pollen grains and mostly striate exine ornamentation (Nazeri 2008;Polyakova and Gataulina 2008;Wrońska-Pilarek and Jagodziński 2011;Wrońska-Pilarek et al 2013, 2019Lechowicz et al 2020). Moreover, intra-generic studies indicated that pollen grains were so similar that usually it was possible to distinguish only a few sections or series and from a few to several individual species, and most often there were groups of taxa with similar pollen characteristics.…”
Section: Discussionmentioning
confidence: 99%